Implementasi Strategi Manajemen Pemasaran Fire Product dalam Optimalisasi Distribusi Rantai Pasok di PT. Amman Mineral Nusa Tengara Barat - Fajar Ramadhan Tidar; Ady Setiawan; Rukin Rukin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This research aims to analyze the implementation of Fire Product marketing management strategies in optimizing supply chain distribution at PT. Amman Mineral Nusa Tenggara Barat. An exploratory case study with a qualitative approach was conducted through semi-structured interviews, participatory observation, and documentation studies involving 20 key informants from various departments. The results show that PT. Amman Mineral implements multi-dimensional marketing strategies with a value-based marketing approach and the "Fire Safety Champion" program that significantly improves distribution efficiency. Five main factors affecting distribution effectiveness include geographical conditions, inter-departmental coordination, technology and information systems, demand fluctuations, and supplier availability and responsiveness. The implementation of product value-based marketing strategies positively correlates with distribution efficiency, marked by a 43% decrease in emergency requests and a 23% reduction in excess inventory without sacrificing availability in critical areas. An integrative model combining demand-based marketing, just-in-time inventory management, and digital monitoring systems is proposed to optimize Fire Product distribution. This research provides theoretical contributions to the development of an integrative marketing management and supply chain model for products with high strategic significance, as well as practical implications for improving distribution efficiency in industries with complex operational characteristics.